Targeting MDM2 for Treatment of Adenoid Cystic Carcinoma - Warner, Kristy A. (Clin Cancer Res, 2016)
PURPOSE: There are no effective treatment options for patients with advanced adenoid cystic carcinoma (ACC). Here, we evaluated the effect of a new small molecule inhibitor of the MDM2-p53 interaction (MI-773) in preclinical models of ACC. EXPERIMENTAL DESIGN: To evaluate the anti-tumor effect of MI-773, we administered it to mice harboring 3 different patient-derived xenograft (PDX) models of ACC expressing functional p53. The effect of MI-773 on MDM2, p53, phospho-p53 and p21 was examined by Western blots in 5 low passage primary human ACC cell lines and in MI-773-treated PDX tumors. RESULTS: Single agent MI-773 caused tumor regression in the 3 PDX models of ACC studied here. For example, we observed a tumor growth inhibition (TGI) index of 127% in UM-PDX-HACC-5 tumors that was associated with an increase in the fraction of apoptotic cells (p=0.015). The number of p53-positive cells was increased in MI-773-treated PDX tumors (p<0.001), with a correspondent shift in p53 localization from the nucleus to the cytoplasm. Western blots demonstrated that MI-773 potently induced expression of p53 and its downstream targets p21, MDM2 and induced phosphorylation of p53 (serine 392) in low passage primary human ACC cells. Notably, MI-773 induced a dose-dependent increase in the fraction of apoptotic ACC cells and in the fraction of cells in the G(1) phase of cell cycle (p<0.05). CONCLUSIONS: Collectively, these data demonstrate that therapeutic inhibition of the MDM2-p53 interaction with MI-773 activates downstream effectors of apoptosis and causes robust tumor regression in preclinical models of adenoid cystic carcinoma.